2008
DOI: 10.1016/j.bbagrm.2007.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of the human soluble epoxide hydrolase gene EPHX2

Abstract: Soluble epoxide hydrolase (sEH) is a multifunctional protein encoded by the EPHX2 gene. The biological functions and enzyme kinetics of sEH have been extensively investigated, however, little is known about its transcriptional regulation and mechanisms of tissue specific expression. Here, a luciferase gene based reporter assay was used to identify the minimal promoter and cis regulatory elements of EPHX2. The minimal promoter was identified as a GC-rich region between nts −374 to +28 with respect to the putati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 61 publications
(87 reference statements)
1
31
0
3
Order By: Relevance
“…sEH expression can be regulated by 15d-PGJ2, homocysteine, angiotensin II, and tyrosine nitration, as well as by peroxisome proliferator-activated receptor-␥ agonists (2,5,6,18,24). Our previous studies showed that sEH upregulation contributes to hypertension and cardiac hypertrophy (3,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…sEH expression can be regulated by 15d-PGJ2, homocysteine, angiotensin II, and tyrosine nitration, as well as by peroxisome proliferator-activated receptor-␥ agonists (2,5,6,18,24). Our previous studies showed that sEH upregulation contributes to hypertension and cardiac hypertrophy (3,23).…”
Section: Discussionmentioning
confidence: 99%
“…The protocol of VSMCs infected with adenovirus sEH (Ad-sEH) or adenovirus-mediated green fluorescent protein (Ad-GFP) has been described elsewhere (3,18,23). The adenovirus was added to the medium and incubated for 24 h. The infection efficiency was detected by RT-PCR and Western blot analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Certainly, the exposure of mice to hypoxia for 3 weeks increased the expression of CYP2C29 and elicited pulmonary vascular remodeling (Pokreisz et al, 2006). Interestingly, the same procedure markedly attenuated the expression of the sEH in vivo and in vitro, most probably via altered binding of specificity protein 1 (Tanaka et al, 2008a) and c-Jun (Ai et al, 2007) to the sEH promoter. It was possible to make a causative link between remodeling and P450 activity because P450 inhibition attenuated the increase in pulmonary vascular muscularization observed over 1 week.…”
Section: F Cytochrome P50-derived Mediators In the Lungmentioning
confidence: 99%
“…The sEH promoter contains several specificity protein 1 (Tanaka et al, 2008a) and activating protein 1 (AP-1) sites (Ai et al, 2007). Methylation of one of the former has been implicated in gene silencing , whereas the activation of AP-1 is implicated in the angiotensin IIinduced upregulation of the enzyme (Ai et al, 2007).…”
Section: B Soluble Epoxide Hydrolasementioning
confidence: 99%
“…Our previous work indicated that AP-1 activation is involved in the transcriptional upregulation of sEH by Ang II in ECs (11). We previously reported that basal promoter activity of sEH varied in different types of cells, of which a proximal Sp1 binding site was critical (25). During the pathophysiological onset of hypertension, Ang II likely induces sEH via AP-1 activation in adult ventricular cardiomyocytes (11).…”
Section: Fig 4 Role Of Seh Inhibitor In Ang Ii-induced Cardiomyocytmentioning
confidence: 99%